RANCANG BANGUN KAMPUNG EKOWISATA BURUNG MALEO GUNUNG (Aepypodius arfakianus) BERBASIS KEARIFAN LOKAL MASYARAKAT HATAM UNTUK MENINGKATKAN EKONOMI DAN KONSERVASI SATWA ENDEMIK PAPUA DI PEGUNUNGAN ARFAK - Agustinus Kilmaskossu (Jurnal Natural, 2014)
The wildlife on earth is increasingly urged by human life, where forest functions are used as residential and agricultural land. Illegal logging causes destruction of habitat and excessive use of wildlife causing damage to ecological functions in general. Uncontrolled utilization of eggs and fowls of wattled brushturkeys will accelerate the extinction of these animals in natural habitats. On the other hand the dependence on protein and economic needs of communities in the Arfak Mountains is high as evidenced by the widespread of hunting activities conducted with various purposes of utilization. Breeding efforts for the purpose of utilization need to be given attention in relation to the conservation and fulfillment of human needs. Efforts to increase the population of the bird are made through the modification of breeding and captive breeding efforts so as to encourage the acceleration of the bird population in nature and on the other hand the community interest in the fulfillment of protein and economic needs can be accommodated. Therefore, basic knowledge of the wisdom of local communities are need to support the sustainability of this bird in nature. Studies of local community wisdom and natural nest site coverage data need to be immediately obtained to fullfil the purpose. This baseline data is a reference to the establishment of appropriate breeding sites and management is expected to increase the acceleration of this bird population in nature as well as economic improvement through an ecotourism village. This research was conducted in Minyambouw District around Arfak Mountains Nature Reserve for 2 years (2013-2014). The first year study aims to find out the location of active nesting sites and strategic location to serve as a breeding model. Some active bird nests of the bird have been found in the forest of Syoubri village and then mapped based on GPS data. In the second year, the collection of cultural data of the community (local wisdom) as the basis of customary rules that bind the community. Some people (50%) still do hunting for family consumption and income. To overcome this, the community agreed and happy to make the bird and its nest as a tourist attraction. In relation to that there is a need to do management of ecological tourism for the community and creation of a captive breeding programme through a hatchery effort on wattled brushturkey birds.